History of Banking in Sudan (Conventional and Islamic): A Critical Review (1903-2019) - Mustafa, Omer Allagabo Omer (International Finance and Banking, 2024)
This paper critically reviews the developmental stages of banking (Conventional and Islamic) in Sudan throughout the last 115 years (1903-2019). Historical and descriptive-analytical approaches were used. Historical data collected from the annual reports of The Central Bank of Sudan and relevant studies were used to describe and compare stages during that period. The results indicated that political instability and ideology changes of the state (e.g., Colonialism, independence and democracy, socialism and Islamic) systems played a significant role in the formation of stages of development of Sudan’s banking systems (e.g., conventional, Islamic, dual system). Moreover, the implementation of the Islamic Sharia Law in 1983 was the original basis for the augmentation of the Islamization of the country’s banking system, particularly as it pertained to the prohibition of charging interest. Under the Comprehensive Peace Agreement (CPA: 2005-2010), the conventional banking (interest rate) in Southern Sudan was restored, whereas the Islamic approach continued in the north. Notwithstanding, all banks were managed by one central bank in the north namely The Central Bank of Sudan. The study highlights the relationship between factors affecting political stability and the growth of stability and the banking system.